Effect of sodium hypochlorite as dentinal pretreatment on bonding strength of adhesive systems - Anelise Fernandes Montagner; Jovito Adiel Skupien; Marciano Freitas Borges; Ivo Krejci; Tissiana Bortolotto; Alexandre Henrique Susin (Wolters Kluwer Medknow Publications, 2015)
Aim: This study aimed to evaluate the effect of sodium hypochlorite (NaOCl) pretreatment on bond strength of adhesive systems to different dentin regions. Materials and Methods: Forty human molars were randomly assigned according to different adhesive systems (Adper Single Bond 2; Clearfil SE Bond; Adper SE Plus; G-Bond), pretreatments (control and NaOCl - deproteinization) and dentin regions (proximal, superficial occlusal [SO] and deep occlusal [DO]), n = 5. Cylindrical cavities were performed at the proximal and occlusal surfaces of each sample. For deproteinization, 10% NaOCl was applied on conditioned dentin for 60 s before the adhesive systems application. Two occlusal and one proximal slice were obtained from each sample and submitted to the push-out test. The mode of fracture was analyzed. The data were subjected to three-way ANOVA and Tukey test (P < 0.05). Results: There was statistically significant difference between the adhesive systems (P < 0.01) and dentin regions (P < 0.01); however, the pretreatment did not significantly affect the bond strength values (P > 0.05). The bond strength values were higher for the proximal surface, followed by SO and later by DO, being influenced by the adhesive system. The two-step self-etch adhesive systems presented the highest bond strength results. Conclusion: The deproteinization pretreatment showed similar bonding effectiveness to the conventional adhesive technique. The dentin region plays a rule on the bond strength values.